A proposed novel approach to the study of the dual-mode mechanism of dyeing nylon with acid dyes - Iijima, T.; Petropoulos, J. H. (Journal of applied polymer science, 2007)
Study of the dual mode mechanism of dyeing nylon with acid dyes, consisting of Langmuir‐type sorption on charged terminal amino groups, accompanied by Nernst‐type uptake, known as “overdyeing,” is subject to complications primarily (but not exclusively) because of structural nonhomogeneity of the polymeric substrate. We present here a system that combines structural simplicity with ease of manipulation of amine content; wherein the nylon substrate is replaced by a liquid phase consisting of a specially selected amine dissolved in a suitable organic solvent. This system displays the characteristic features of the aforementioned dual mode dyeing mechanism, as shown by experimental data of the uptake of C.I. Orange 7 as a function of aqueous dye concentration and amine concentration in the organic phase. © 2006 Wiley Periodicals, Inc. J Appl Polym Sci 103: 1055–1057, 2007